Improving postural stability through proprioceptive training in dogs - Lutonsky, Christiane; Affenzeller, Nadja; Aghapour, Masoud; Wegscheider, Julia; Peham, Christian; Tichy, Alexander; Bockstahler, Barbara (Frontiers in Veterinary Science, 2025)
Postural stability (PS) is essential for functional mobility and rehabilitation. While posturography and center of pressure (COP) parameters are commonly used to assess PS, little is known about the effects of proprioceptive training programs in dogs. This study aimed to evaluate the effects of a 4-week training program in dogs on a motorized proprioceptive training platform which creates a curved movement in the 3 planes of space that follows Elispheric® trajectories (Imoove-vet®, Allcare Innovations, France). Twenty dogs were divided into a training group and a control group. Five conventional COP parameters were measured under 4 different conditions (neutral, uphill, downhill, perturbed standing) pre- and post-intervention. The primary outcomes included statistically significant improvements in craniocaudal (CCD%), mediolateral (MLD%) displacement, and support surface (SS%). Dogs participating in the training group showed statistically significant reductions in COP excursions post-intervention, specifically CCD% during perturbed standing, MLD% during downhill standing, and SS% during uphill standing. Compared to the control group, the training group showed a statistically significant reduction in CCD% and SS% during uphill standing, and MLD% during downhill standing post-intervention. No statistically significant changes were observed, and effect sizes remained below Cohen’s d < 0.5 in the control group. In contrast, large training effects (d > 0.8) for all significantly decreased parameters were found in the training group. The results support the effectiveness of proprioceptive training in improving PS specifically under biomechanically challenging conditions highlighting the relevance of including these tasks in PS assessment and training protocols. Further research is warranted in orthopedically and neurologically diseased populations to explore therapeutic applications.